The development of English vocabulary with the picture me reading technique for grade 4 students - Sanchompoo, Supaporn; Prasertsang, Parichart (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The purposes of the research were to 1) develop the activity of English vocabulary learning with the picture me reading technique for grade 4 students with the criteria efficiency of 75/75, 2) compare the learning achievements for grade 4 students between before and after learning with Picture Me Reading, 3) compare the activity of English vocabulary learning using with picture me reading technique for grade 4 students with 75% criteria, and 4) study the students' satisfaction towards the activity of English vocabulary learning using with picture me reading technique for grade 4 students. Fifteen students of Ban Khoi School, obtained by cluster random sampling participated in this study. The research instruments were 12 plans of activity for English vocabulary learning 20 multiple-choice, a 4-choice achievement test, and the satisfaction questionnaire. The data were analyzed using basic statistics by percentage, mean, standard deviation, and t-test statistics. The results showed that learning activities consisted of 4 learning stages which had efficiency criteria 79.31/75.35. The academic achievement of students after learning was higher than before at the 0.5 level of significantly statistics. Students had score after learning activities higher than the criterion of 75%, and they had satisfaction was at the high level.